Representation of Muslim Women in Manga Satoko & Nada - Drajat, Aldrie Alman; Kurnia, Lilawati (Sekolah Pascasarjana Institut Kesenian Jakarta, 2018)
Since the beginning of the 21st century, the mass media has been inclined towards constructing a negative image of Islam, which is internalized by the societies in countries where Moslems are in the minority, including Japan. Modern Japanese society is very dependent on the mass media for quick and concise information. The image of Islam internalized by the Japanese society is the one associated with terrorism and backwardness. This paper presents a different representation of Islam as reflected in a Japanese manga Satoko & Nada which focuses on the friendship between a Japanese girl Satoko and an Arab girl Nada in the United States. Visual and verbal analysis on the manga reveals an uncommon image of Moslem women which is not inclined towards excessive self-limitation. The manga shows that Moslem women really have a degree of freedom to express themselves, albeit with some limitation. Besides that, it also features open-minded Moslem women who are not hesitant to welcome modernization. Those characteristics are very different from the popular beliefs about Moslem women as constructed by mainstream mass media. As one of Japanese popular media, manga Satoko & Nada serves as a counter narrative by offering a different image of Moslem women as never shown in common mass media. Mulai dari dekade 2000-an, Media massa mengonstruksi citra Islam yang cenderung negatif dan telah terinternalisasi pada masyarakat di negara-negara non-mayoritas Islam, termasuk Jepang. Masyarakat Jepang modern sangat tergantung pada media massa untuk mendapatkan informasi dengan ringkas dan cepat. Imaji Islam yang terinternalisasi di dalam masyarakat Jepang pun terasosiasi pada terorisme dan keterbelakangan. Dalam makalah ini akan dipaparkan representasi muslim yang berbeda dalam manga Jepang berjudul Satoko&Nada yang menceritakan persahabatan Satoko, gadis yang berasal dari Jepang dan Nada, gadis yang berasal dari Arab di Amerika Serikat. Dari analisis visual dan verbal terlihat konstruksi identitas wanita muslim yang tidak sepenuhnya tertutup. Diperlihatkan bahwa wanita muslim di dalam Satoko&Nada memiliki kebebasan untuk mengekspresikan dirinya walaupun terbatas. Selain itu diperlihatkan pula wanita muslim yang memiliki pemikiran terbuka dan mengikuti arus modernisasi. Karakteristik-karakteristik tersebut sangat berlawanan dengan popular belief mengenai wanita muslim yang telah dikonstruksi dalam media massa. Manga Satoko&Nada sebagai salah satu dari media populer Jepang menyampaikan wacana tandingan mengenai wanita muslim yang tidak pernah terlihat di dalam media massa.